De l’impact du TGV sur deux quartiers de gare : Nancy Grand Coeur et Metz Amphithéâtre - Anne Hecker (Belgeo)
The arrival of the East European TGV in the heart of Metz and Nancy provided the two rival cities of Lorraine with an opportunity to reshape their landscape and to requalify the railway station areas. In spite of very different situations, the evolution of both projects leads them to a strong convergence. Still, they differ on one point: while one of them tries to merge the new city quarter into the city centre, the other focuses on realizing a new heart for the agglomeration, and thus risks devitalizing the old centre. By betting on the structuring effect of the TGV, both could lead to a semi-failure due to overambitious developments.